ЭЛЕКТРОН ЎҚУВ РЕСУРСЛАРИДАН ТАЪЛИМ-ТАРБИЯ ИШЛАРИДА ФОЙДАЛАНИШ АФЗАЛЛИКЛАРИ - Казбекова, Э.М. (SCIENCE and SOCIETY, 2020)
The article refers to the advantages of using interactive complexes in the organization of educational and upbringing work among pupils of preschool Educational Establishment.